Writer's body and fictional bodies : violence and abused bodies in the French-speaking Central African novel - (:unkn) unknown (My University, 2023)
Francophone literature in Central Africa is a heterogeneous group of productions and production spaces linked by the language of the former colonizer. This socio-historical link suggests that the areas concerned, i.e. Cameroon, Congo-Brazzaville, Gabon and Zaire, which were chosen for this study, form universes that are not independent of their social, historical and corporeal conditions of engendering. Born and socialized in this region, Central African writers are, to varying degrees, sensitive to social transformations, and in particular to mutations in the various forms of violence that weaken social structures and brutalize bodies. From this perspective, bodies appear as means of experimentation, expression and evaluation of symbolic violence. Our guiding hypothesis is that the treatment of violence through bodies, and the treatment of bodies themselves, thus operate as important vectors of Francophone African novel writing, as our corpus at least illustrates. As vectors of writing and vectors of the novel's society, violent bodies appear as properly socioliterary bodies.The representations of violated bodies and the descriptions of the tensiogenic environments in which the characters evolve maintain, or so this thesis attempts to demonstrate, similarities with the writer's own body. We shall see that some authors include writer characters in their novels, whose physicality and stance on violence correspond to those of the writers themselves. More generally, as Pierre Bourdieu argues, the literary positions taken by writers are expressed in extraliterary political acts and discourses, "which means that we must reject the alternative between an internal reading of the work and an explanation by the social conditions of its production or consumption".
Keywords: African Research